2022
DOI: 10.1128/jvi.00412-22
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 N Protein Antagonizes Stress Granule Assembly and IFN Production by Interacting with G3BPs to Facilitate Viral Replication

Abstract: In this study, by in vitro assay and live SARS-CoV-2 virus infection, we provide solid evidence that the SARS-CoV-2 NP associates with G3BP1 and G3BP2 in vitro and in vivo . NP SARS-CoV-2 could efficiently suppress G3BP-mediated SG formation and potentiate viral infection by overcoming antiviral innate immunity mediated by G3BP1 in A549 cell lines and G3BP1 conditional knockout mice ( g3bp1 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 31 publications
10
58
0
Order By: Relevance
“…To investigate if inflammatory pathway regulation by the VOCs was associated with viral protein expression, as we found previously for Alpha ( 14 ), we correlated viral protein and RNA levels with pathway module regulation from our integrative computational analysis and ranked viral genes according to their correlation with inflammatory response modules (modules 8, 13, 31, 43, and 53). Expression of N and Orf6, both well-studied innate immune antagonist proteins ( 5355 ), were the most anticorrelated with inflammatory response modules, consistent with the notion that their enhanced expression contributes to the suppression of the host innate immune response across the VOCs (Fig. 6J, S7D).…”
Section: Main Textsupporting
confidence: 78%
“…To investigate if inflammatory pathway regulation by the VOCs was associated with viral protein expression, as we found previously for Alpha ( 14 ), we correlated viral protein and RNA levels with pathway module regulation from our integrative computational analysis and ranked viral genes according to their correlation with inflammatory response modules (modules 8, 13, 31, 43, and 53). Expression of N and Orf6, both well-studied innate immune antagonist proteins ( 5355 ), were the most anticorrelated with inflammatory response modules, consistent with the notion that their enhanced expression contributes to the suppression of the host innate immune response across the VOCs (Fig. 6J, S7D).…”
Section: Main Textsupporting
confidence: 78%
“…Also, while host cell protein synthesis should best be inhibited and kept at a minimum, efficient unperturbed production of viral proteins must be ensured by preventing translational suppression due to activation of the OAS/RNaseL pathway and PKR-dependent induction of the ISR. Recent publications implicated SARS-CoV-2 N protein as an inhibitor of SG formation and an RLR antagonist (33)(34)(35)(60)(61)(62). Here, we confirmed and extended these observations using a convenient procedure to assess PKR-induced ISR activation based on transfection of ISR-inducing plasmid DNA to drive the expression of putative ISR antagonists genetically fused to EGFP.…”
Section: Discussionsupporting
confidence: 78%
“…G3BP1/2-N association through subdomain N1a (39, 50, 51) and N2b, directly via protein-protein interaction and/or indirectly, promoted by RNA binding (70), may well hamper SG assembly and/or thereby impede recruitment and SG-facilitated activation of RLRs and PKR (20-23) already early in infection when levels of N are still low. Indeed, this would be consistent with observations by others (35, 70) that SARS-CoV-2 inhibits induction of type I IFNs by targeting G3BP1 and suppressing SG-associated RLR activation. It has also been proposed that N counteracts the intracellular antiviral response by interfering with innate immune signaling at the level of MAVS and impeding MAVS-RIG-I association (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-iORF3, encompassing the C-terminal N2b domain and surrounding linker regions, inhibits the dsRNA-dependent IFN-response (Mears et al, BioRxiv DOI=10.1101/2022.04.20.488895), and overexpression experiments in our laboratory showed that it also blocks the ISR (Aloise et al, BioRxiv DOI=10.1101/2022.09.02.506332). In interactome studies, SARS-CoV-2 N was found to bind to SG assembly factors G3BP1 and G3BP2 via its N-terminal domain N1a, suggesting that it may also directly suppress SG formation 61 , 62 , 63• , 64 , 65 , 66 , 67• .…”
Section: Coronavirus Isr Antagonistsmentioning
confidence: 99%